FACTORS THAT INFLUENCE THE LOYALTY OF A BUSINESS CUSTOMER USING A PACKAGE DELIVERY SERVICE IN THAILAND: A CONCEPTUAL MODEL - Sethapol Lieophairot; Samart Deebhijarn; Aukkapong Sukkamart (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This paper proposes a six-hypothesis conceptual model to investigate customer loyalty within the Thai courier, express, and parcel (CEP) delivery sector. Globally, in 2020 this was a $326 billion industry employing nearly 2.5 million packages delivering 60.7 billion parcels. Thailand as a leading commercial hub in many regional economic sectors relies heavily on both domestic and international CEP delivery services to keep e-commerce and supply chain wheels rolling. Therefore, the authors' proposed study includes an investigation into the four primary latent variables of service innovation (SI), service quality (SQ), service satisfaction (SS), and customer loyalty (LT) and the theory supported 17 observed variables. The proposed research instrument is a questionnaire for use in the quantitative analysis. Initial sample size theory research indicates a sample of 340 - 400 should suffice. Qualitative analysis will employ the use of LISREL 9.1 software from which the goodness-of-fit (GOF) statistics will be analyzed for the confirmatory factor analysis (CFA). Descriptive statistics are anticipated to include the mean (???? ), standard deviation (SD), kurtosis, and skewness for each of the items surveyed. From the outcomes of these processes, a final structural equation model (SEM) will be undertaken for results interpretation. It is also suggested that the study will be a significant contribution to the region's literature on courier services and what makes their customers loyal.